The Effectiveness of Using Instagram Social Media in Increasing Sales at Loen Cakes - Meidyrianto, Rizky Kukuh (Devotion : Journal of Research and Community Service, 2025)
This study evaluates Instagram’s effectiveness in enhancing brand awareness and purchasing interest for Lien Cakes, a culinary business, amid Indonesia’s growing digital marketplace. Employing a quantitative approach with a correlational design, data were collected via questionnaires from 100 active Instagram users, including employees and consumers, to analyze engagement patterns and promotional impact. Findings reveal that 59% of employees purchased via Instagram for convenience, while 81% reported satisfaction, underscoring the platform’s sales potential. Visually creative content and influencer collaborations significantly boosted engagement, though low employee adoption (53% used Instagram for <1 year) highlighted training needs. The study contributes practical insights for optimizing Instagram strategies in niche culinary markets, emphasizing demographic-specific content and employee upskilling. Implications suggest that businesses integrate Instagram’s interactive features (e.g., Stories, UGC) with targeted training to maximize reach and loyalty, while future research could explore AI-driven personalization or cross-platform comparisons.